Gallic acid liposome and powder gels improved wound healing in wistar rats (Annals of Medical Research, 2021)
Aim: Gallic acid is an anti-inflammatory and antioxidant agent which could provide beneficial effects in preventing periodontal inflammation and improve wound healing. The present study aimed to evaluate the effects of gallic acid on experimental palatal wound model in Wistar rats.Material and Methods: 60 female Wistar rats were divided into three main study groups as the control group (C, n=24), gallic acid powder gel administered group (GP, n=18), and gallic acid liposome administered group (GL, n=18). Standardized palatal wounds of 5-mm diameter were created in all rats. Control rats received vehicle gel, and the other groups received either GP or GL gels. Control rats were sacrificed on days 0, 7, 14, and 21. GP and GL groups were sacrificed on days 7, 14, and 21. Hematoxylin-eosin staining was performed, and fibroblast cell counts and inflammatory cell infiltration in the wound area were evaluated. Transforming growth factor (TGF)-β expressions were determined via immunohistochemistry.Results: C, GP, and GL groups had a similar decrease in wound area apart from 21st day, which GL had significantly lower wound area compared to the control group. Unhealed wound area was significantly lower on the 14th and 21st days in gallic acid groups. GP and GL groups had significantly higher fibroblast cell counts on all days compared to the C group. GL had significantly highest counts even compared to GP groups. Inflammatory cell infiltration was higher on the 7th day compared to14th and 21st days in all groups. Gallic acid groups exhibited lower inflammatory cell counts on 7th and 21st days. TGF-β levels significantly increased in GP and GL groups on 7th and 14th days. Conclusion: Within limitations of the present study, it can be concluded that gallic acid in both powder and liposome forms increased fibroblast cell counts and decreased late inflammation along with increased TGF-β expressions in the wound healing process.
Keywords: Anti-inflammatory; antioxidants; gallic acid; wound healing